Hemodynamic Effect of 2% Lidocaine with 1:80,000 Epinephrine Infiltration in Maxillofacial Surgeries under General Anesthesia - Baratollah Shaban; Elham Moradi; Amir Hossein Nejat; Somayeh Sabzali Zanjanhkhah; Touraj Vaezi (Mashhad University of Medical Sciences, 2013)
Introduction: Epinephrine-containing lidocaine is the most used anestheic drug in dentistry. The aim of this study was to investigate the hemodynamic changes following local infiltration of 2% lidocaine with 1:80,000 epinephrine in subjects undergoing orthognatic surgery under general anesthesia. Methods: Twenty five patients without any systemic disease participated. After general anesthesia, two cartridges of 2% lidocaine + 1:80,000 epinephrine were infiltrated around the surgery site. Systolic (SBP) and diastolic (DBP) blood pressure, mean arterial blood pressure (MAP), heart rate (HR), and blood sugar (BS) were measured in three stages: before the injection (M1), at the end of injection (M2), and 10 min after injection (M3). Results: No significant difference observed in SBP, DBP, and MAP at the end of injection and 10 min later. HR was increased significantly after injection and remained significantly higher than baseline after 10 min. BS increased slightly at the end of injection and continued to increase after 10 min. However, changes in BS were not significant. Conclusion: Using two cartridges of epinephrine-containing lidocaine have slight systemic changes in healthy subjects; as a result, this dosage could be used in patients with cardiovascular complications undergoing general anesthesia.